2005
DOI: 10.1074/jbc.m408403200
|View full text |Cite
|
Sign up to set email alerts
|

Single Amino Acid Mutations in the Cadherin Receptor from Heliothis virescens Affect Its Toxin Binding Ability to Cry1A Toxins

Abstract: Bacillus thuringiensisto an alanine, however, increased the Cry1Ac affinity 10-fold primarily due to an increase on rate. The L1425R mutant can result from a single nucleotide mutation, CTG 3 CGG, suggesting that these mutants, which have decreased toxin binding, may lead to Cry1A resistance in insects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
145
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(156 citation statements)
references
References 46 publications
8
145
3
Order By: Relevance
“…Mutants-Previously, we reported that loop 3 of Cry1Ab toxin showed a hydropathic complementary pattern with the binding epitope of H. virescens cadherin, suggesting a putative interaction through a complementary hydropathic profile (17). Here we introduce amino acid substitutions in loop 3 of Cry1Ab toxin designed to disrupt the hydropathic profile of this region.…”
Section: Construction Of Cry1ab Loopmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutants-Previously, we reported that loop 3 of Cry1Ab toxin showed a hydropathic complementary pattern with the binding epitope of H. virescens cadherin, suggesting a putative interaction through a complementary hydropathic profile (17). Here we introduce amino acid substitutions in loop 3 of Cry1Ab toxin designed to disrupt the hydropathic profile of this region.…”
Section: Construction Of Cry1ab Loopmentioning
confidence: 99%
“…Insect cadherins are composed of an ectodomain formed by 11 or 12 cadherin repeats (CRs), a transmembrane domain, and an intracellular domain (14). The exposed loops of Cry1A domain II have been directly involved in binding with cadherin in M. sexta, H. virescens, and B. mori (15)(16)(17)(18). Three Cry1Ab binding sites were mapped in CR7, CR11, and CR12 of the M. sexta Bt-R 1 (15,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a major threat for the use of Bt toxins in transgenic plants is the appearance of insect resistance. It has been demonstrated that a single nucleotide change in the Heliothis virescens cadherin receptor gene produces an amino acid change that abolishes Cry1A toxin binding [35]. Therefore the need of developing an efficient method that allows genetic evolution of Cry toxins to kill novel targets or to recover toxicity to resistant insects, in the case of the appearance of resistance in the field, will be greatly desirable.…”
Section: Displaying Cry Toxins In Phages and Selection Of Novel Variantsmentioning
confidence: 99%
“…Additionally, knockout of a b-1,3 galactosyltransferase from the mutagenized Bt resistant 5 (bre5) line of Caenorhabditis elegans resulted in resistance to Bt toxins (Griffitts et al 2001), which reiterated the role that postranslational glycosylation may play in toxin-binding of receptor proteins (Knowles et al 1991;Jurat-Fuentes et al 2002). Mutations in the receptors, aminopeptidase N and cadherin, were also shown to result in larval Bt toxin-resistance traits among species of Lepidoptera (Gahan et al 2001;Morin et al 2003;Herrero et al 2005;Xie et al 2005;Zhang et al 2009). In contrast, analysis of the Cry1Ac-and Cry2Aa-resistant CP73 strain of Heliothis virescens indicated that neither cadherin nor aminopeptidase N receptor genes contributed to resistance traits Heckel et al 2007).…”
Section: Introductionmentioning
confidence: 99%